Perspectives for improvement of karate stance performance on the basis of electromyogram analysis - Vovkanych, L.; Kindzer, B.; Fedkiv, M. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. The performance of exercises could be significantly improved on the basis of a detailed analysis of muscle activity, which can be studied by registering its electrical activity. We aimed to examine the activity of some of the muscles of karatekas during the performance of Kyokushinkai karate stances. Methods. Participants - 16 highly qualified (1 dan, 12-17 years` experience) male Kyokushinkai karate athletes, aged 18-25. Surface electromyogram (sEMG) was recorded during the basic Fudo dachi and Kokutsu dachi stances. The electrical activity of m. gluteus maximus, m. rectus femoris, m. biceps femoris, m. semitendinosus, m. gasterocnemius (caput lateralis), m. tibialis anterior was registered. Results. We found low (up to 38% of the maximum) levels and right-left symmetry of the mean amplitude and frequency of sEMG in the case of Fudo dachi. This is in good agreement with the proper technique for performing the stance. However, the electrical activity of some leg flexors (up to 23%) and foot flexors (up to 26%) was unexpectedly high, which may speed up the development of fatigue. We found higher levels of sEMG indices in the left ankle dorsiflexors and left knee flexors and extensors, as well as the right ankle plantarflexors in the Kokutsu dachi as compared to the Fudo dachi stance. The highest level of sEMG amplitude was registered for the m. gasterocnemius d. (up to 58%) and m. tibialis anterior s. (up 46% to). Bilateral asymmetry in the sEMG indexes was found for the majority of the leg muscles, except m. semitendinosus. Unexpectedly high-level activity in the ankle plantarflexor in the front leg was found. Conclusions. The comparison of the sEMG data with the descriptions of the stance performance allowed us to elaborate the models of muscle activity during exercises and to assume some peculiarities in the technique of the performance of the stances.